The influence of ultimate ownership concentration on leverage - Hong, Kok Chee; Hooy, Chee-Wooi; Ooi, Chai-Aun (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper investigates the relationship between ultimate ownership concentration and the extent of leverage in the context of Malaysia. The data of this study include 478 publicly listed firms from2001 to 2012. The results show that ultimate ownership concentration has U-shaped relationship with leverage, with the turning point being at the ownership concentration of 42%. Based on signalling theory, the results show that a moderate extent of ultimate ownership concentration tends to adopt lower leverage for they have higher incentives to self-monitor managerial opportunistic decision making; by contrast, an ultimate owner who holds excessively high concentration of shareholdings shows self-benefitting behaviour, with the owner tending to adopt higher leverage to sustain the loss of firm value from expropriation. However, higher institutional ownership concentration plays a significant monitoring role over the owner’s opportunistic behaviour through the signalling of lower leverage even when the shareholding of ultimate owner is excessively large.